FUNCTIONAL OUTCOMES OF PROXIMAL HUMERUS FRACTURE USING PHILOS - HAQ , SU; SAEED , M; QASIM , M; HUSSAIN , M (Biological and Clinical Sciences Research Journal, 2024)
Proximal humeral fractures are among the most common upper extremity fractures, particularly in adults, and their management remains a challenge. The Proximal Humerus Internal Locking System (PHILOS) plate fixation is widely used for these fractures, offering stability and enabling early mobilization. However, functional outcomes and potential complications require thorough evaluation to ensure optimal patient care. Objective: To assess the functional outcomes of Proximal Humerus Internal Locking System (PHILOS) plate fixation in patients with proximal humeral fractures. Methods: This prospective observational study was carried out at the orthopaedic department from July 2023 to July 2024. Participants included patients aged 20 years and older with proximal humeral fractures. All patients underwent PHILOS plate fixation performed by experienced orthopaedic surgeons. Functional outcomes were assessed using the Constant-Murley score at 6 months postoperatively, with outcomes categorized as Excellent, Good, Fair, or Poor. Complications, including avascular necrosis, implant-related issues, subacromial impingement, malunion, and nonunion, were recorded. Results: Mean age was 42.98 ± 14.40 years. Functional outcomes were classified as Excellent in 32% of cases, Good in 44%, Fair in 14%, and Poor in 10%. Complications included avascular necrosis in 12%, implant-related complications in 8%, subacromial impingement in 4%, and malunion in 10%. Conclusion: PHILOS plate fixation for proximal humeral fractures provides favourable functional outcomes and minimum complications.